Hubungan Kebijakan Pemberdayaan Aparat Pemerintah Desa Dengan Percepatan Keberhasilan Pembangunan - Manabung, Shinta; Lengkong, Florence Daicy; Rompas, Sonny (Sam Ratulangi University, 2015)
Abstract: Since the implementation of the Act. Number 32 of 2004 on Regional Government, the localgovernment in Indonesia has entered a new era known as the era of regional autonomy. This bringsthe consequence that in order to optimize or accelerate the success of development in various regions,including rural development, required the support or participation of all components; and one ofthemain component that exist at the village level is the village officails. This study aimed to: